INTEGRATING ETHICS, REASON, AND SOCIETY: A COMPARATIVE LITERATURE REVIEW OF EDUCATIONAL THOUGHT IN AL-GHAZALI, AL-FARABI, AND IBN KHALDUN - Fiksi Juita; Zuhdiyah Zuhdiyah; Maryamah Maryamah; Nyayu Soraya (Jurnal Konseling Pendidikan Islam, 2026)
This study examines the educational thought of classical Islamic scholars—Al-Ghazali, Al-Farabi, and Ibn Khaldun—and its relevance to contemporary Islamic education. The research employs a literature review approach by analyzing scholarly articles published between 2020 and 2025 retrieved from Google Scholar with active DOI references. The analysis focuses on identifying the key educational concepts proposed by these thinkers and exploring how their ideas contribute to the philosophical foundations of Islamic education. The findings reveal that classical Islamic educational thought emphasizes a holistic approach to human development that integrates moral, intellectual, and social dimensions. Al-Ghazali highlights the importance of moral and spiritual education through the cultivation of character and ethical values. Al-Farabi emphasizes rational inquiry and philosophical understanding as the foundation for building virtuous citizens and a harmonious society. Meanwhile, Ibn Khaldun introduces a sociological perspective that links education with cultural transmission and the development of civilization. The synthesis of these perspectives demonstrates that classical Islamic educational philosophy offers an integrative framework that remains relevant for addressing contemporary educational challenges. Therefore, revisiting the educational ideas of these scholars can provide valuable insights for developing a balanced and holistic model of Islamic education in modern contexts.